THE ENHANCEMENT OF STUDENTS’ SKILL IN CLASSIFYING AND CONCEPT MASTERY IN SALT HYDROLYSIS MATERIAL THROUGH PROBLEM SOLVING LEARNING MODEL - Esty Indriyani Safitri; Ila Rosilawati; Tasviri Efkar (Universitas Lampung, 2012)
The purpose of this research is to find out effectiveness of problem solving learning model on salt hydrolysis material in improve the skill of classifying and concept mastery. The population of the research was all students in XI science class in SMAN I Way Jepara number in 120 students. The samples were 30 students in XI science 3 class and 30 students in XI science 4 that have equal academic abilities. This research was a quasi experiment using non equivalent (pretest-postest) control group design. Effectiveness of learning problem solving was measured based on significant gain improvements, and analyze of data using difference of two averages test. The results showed that average value of n-Gain of the skill of clasifying in experiment and control class were 0.67 and 0.42; and average value of n-Gain for concept mastery in experiment and control class were 0.62 and 0.19. The result of difference of two averages test showed that the class used problem solving had higher skill in clasify and concept mastery than class with conventional learning model. This is indicated that problem solving learning model was more effective in improving student’s skill in clasify and concept mastery than conventional learning model.Keywords: problem solving, salt hydrolysis material, improve the skill of classifying and concept mastery